The foreign language studies at Universidad Central «Marta Abreu» de Las Villas in the seventh anniversary of its foundation (Islas, 2022)
ABSTRACTIntroduction: This article aims to expose how these studies have evolved and contributed to the development of this institution in the seventy years of its foundation. There have been considered aspects about the administrative organization in charge of planning and developing the teaching and learning process, undergraduate and postgraduate teaching, as well as activities related to research, publications and participation in improvement courses and events, the collaboration provided by the language teachers, the complementary activities carried out and the distinctions and recognitions received by them.Methods: Document analysis, interview and survey were used as methods in the study.Results: The article recognizes professors who have given prestige to the institution by participating in the training of many professionals and offering their knowledge and devotion to the work carried out at Universidad Central «Marta Abreu» de Las Villas.Conclusions: It is concluded that foreign language studies at Universidad Central «Marta Abreu» de Las Villas have distinguished themselves by being present in the seventy years of academic, research and social life of this institution, and by accompanying the academic training of multiple generations of students and professionals.
Keywords: foreign language studies; Universidad Central «Marta Abreu» de Las Villas; 70 years of foundation